KOMPRES HANGAT JAHE TERHADAP PENURUNAN SKALA NYERI PENDERITA GOUT DI DUSUN BOGOR, MANYARAN, WONOGIRI - Nita Yunianti Ratnasari; Tamara Febriana (Jurnal Keperawatan GSH, 2020)
Gout is a metabolic disease caused by excess levels of uric acid compounds in the body, either due to overproduction, lack of elimination, or increased intake of purines that can cause inflammation so that it can cause pain in gout sufferers. In complementary nursing there are herbal therapies where no pharmacological ingredients are used. Herbal therapy used in the case of gout this time is ginger. Ginger has many benefits, one of which is that it can reduce pain in joint pain or gout. The method used in this research is descriptive case study which is one type of strategy in qualitative research, with a case study research approach (case study). The population in this study is the residents of Bogor Hamlet, Manyaran District, Wonogiri Regency who suffer from Gout pain. Sample of 3 respondents. The instrument uses standard operational procedures (SOP), pain measurement with NRS (Numeric Rating Scale) and observation sheets. Observations that have been made from all respondents indicate that after a warm ginger compress was made for 3 days there was a decrease in pain scale on all respondents. Respondent 1 from pain scale 7 to pain scale 4. Respondent 2 from pain scale 5 to pain scale 1. Respondent 3 from pain scale 6 to pain scale 2. The results of the analysis conducted from all respondents obtained data that after a warm ginger compress was done, all respondents experienced changes namely reduced joint pain, throbbing pain reduced. Thus the problem was partly resolved and the intervention continued.